1984
DOI: 10.1155/lc.5.119
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulations ofViscosity Dependent MolecularRelaxation Processes

Abstract: The dependence of excited-state lifetime, fluorescence quantum yield and isomerization rate of organic dye molecules on solvent viscosity has been a subject of numerous experimental and theoretical investigations. To explain the viscosity dependence of excited-state lifetime in this paper the temporal behavior of the excited state population is calculated for several models of the molecular relaxation process by a computer simulation incorporating both the stochastical motion of large molecular parts in the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
(7 reference statements)
1
15
0
Order By: Relevance
“…This value compared well with the value of 2/3 predicted by Forster and Hoffmann 26 . Typical slope values range from 0.2 to 1.4 for different rotors 27 . We found that below 20 cP, the fluorescence lifetime and quantum yield were minimally variant.…”
Section: Resultsmentioning
confidence: 99%
“…This value compared well with the value of 2/3 predicted by Forster and Hoffmann 26 . Typical slope values range from 0.2 to 1.4 for different rotors 27 . We found that below 20 cP, the fluorescence lifetime and quantum yield were minimally variant.…”
Section: Resultsmentioning
confidence: 99%
“…12). Typical γ -values range between 0.2 and 1.4 97. Fluorescent compounds with high lifetime sensitivity to viscosity are called molecular rotors 98-101.…”
Section: Theory Of Fluorescence Lifetime and Processes Affecting Flmentioning
confidence: 99%
“…A plot of log F f , or log t f as a function of log h should yield a straight line with a slope of a [62,63] which serves as a calibration graph to convert F f or t f into h.…”
Section: Development Of the Theoretical Background: Fluorescence Anismentioning
confidence: 99%